2011
DOI: 10.1111/j.1365-2222.2011.03818.x
|View full text |Cite
|
Sign up to set email alerts
|

Can component‐based microarray replace fluorescent enzimoimmunoassay in the diagnosis of grass and cypress pollen allergy?

Abstract: Component-based microarray ISAC CRD103 and whole-allergen CAP showed high Se and Sp diagnosing equally grass and cypress pollen allergy. The cut-off point for each allergen should be properly applied for both techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 16 publications
0
18
1
Order By: Relevance
“…For example, ImmunoCAP and ISAC tests have a similar sensitivity and specificity in patients diagnosed with grass and cypress pollen allergy on the basis of clinical history and SPTs [11]. SPT and ImmunoCAP tests are generally comparable in predicting or defining symptomatic food hypersensitivity [12].…”
Section: Discussionmentioning
confidence: 99%
“…For example, ImmunoCAP and ISAC tests have a similar sensitivity and specificity in patients diagnosed with grass and cypress pollen allergy on the basis of clinical history and SPTs [11]. SPT and ImmunoCAP tests are generally comparable in predicting or defining symptomatic food hypersensitivity [12].…”
Section: Discussionmentioning
confidence: 99%
“…Although not much data on the diagnostic accuracy of the microarray ISAC in pollen allergy is available, we decided to use this approach because of the possibility it provides to analyze a wide spectrum of pollen-derived component sensitizations. Furthermore, some recent studies have shown similar performances for component-based microarray ISAC and whole-allergen CAP system detection, reporting both high sensitivity and specificity for pollen allergens [6,7]. …”
Section: Introductionmentioning
confidence: 99%
“…Results were expressed as ISAC standardized units (ISU). We did not consider the quantity of the detected specific IgE in further evaluations - results greater than or equal to 0.3 ISU/l were taken as positive [6]. …”
Section: Methodsmentioning
confidence: 99%
“…Each ISAC chip can test four sera for all 130 allergens using~50 μL serum and the results are expressed in ISAC Standardized Units (ISU). In comparative diagnostic studies, the ISAC chip has shown a good correlation with fluorescent immunoassay (ImmunoCAP) for pollen and latex allergy and~78 % concordance when tested against a wider panel of 15 allergens [23][24][25]. Proof-of-principle for using bead suspension arrays for IgE antibody and total IgE measurement on the Luminex xMAP platform has been demonstrated [26].…”
Section: Molecular Diagnosticsmentioning
confidence: 98%